2023
DOI: 10.3389/fpls.2023.1285456
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive metabolome and transcriptome analyses demonstrate divergent anthocyanin and carotenoid accumulation in fruits of wild and cultivated loquats

Wenbing Su,
Changqing Zhu,
Zhongqi Fan
et al.

Abstract: Eriobotrya is an evergreen fruit tree native to South-West China and adjacent countries. There are more than 26 loquat species known in this genus, while E. japonica is the only species yet domesticated to produce fresh fruits from late spring to early summer. Fruits of cultivated loquat are usually orange colored, in contrast to the red color of fruits of wild E. henryi (EH). However, the mechanisms of fruit pigment formation during loquat evolution are yet to be elucidated. To understand these, targeted caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In fact, carotenoids also belong to terpenoids, and there have been extensive studies on the relationship between the carotenoid and flavonoid biosynthesis pathways. A recent study on the pigments of wild loquats and cultivated varieties has demonstrated that the content of carotenoids and flavonoids in the flesh displays a significant opposing trend in the process of evolution, indicating a potential metabolic flux in the fruit ( Su et al., 2023 ). Analogously, the flavonoid and carotenoid biosynthetic pathways affect fruit quality by competing for metabolic flux in SlPSY1 loss-of-function mutants of tomato ( Cao et al., 2023 ), which is the same as the effect of PSY2A deletion in TBW in our previous study ( Song et al., 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, carotenoids also belong to terpenoids, and there have been extensive studies on the relationship between the carotenoid and flavonoid biosynthesis pathways. A recent study on the pigments of wild loquats and cultivated varieties has demonstrated that the content of carotenoids and flavonoids in the flesh displays a significant opposing trend in the process of evolution, indicating a potential metabolic flux in the fruit ( Su et al., 2023 ). Analogously, the flavonoid and carotenoid biosynthetic pathways affect fruit quality by competing for metabolic flux in SlPSY1 loss-of-function mutants of tomato ( Cao et al., 2023 ), which is the same as the effect of PSY2A deletion in TBW in our previous study ( Song et al., 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids, including lycopene and a range of alpha, beta, gamma, and delta carotenoids, undergo synthesis from isoprenoids (IPPs) via enzymatic catalysis. The accumulation of beta-carotene, violaxanthin palmitate, and rubixanthin laurate in Eriobotrya was regulated by the phytoene synthase ( PSY ), Zeta-carotene desaturase ( ZDS ), and zeta-carotene isomerase ( ZEP ) genes ( Su et al., 2023 ). The PSY , Lycopene cyclase/phytoene synthase ( LCYE ), and ZDS were the key genes that regulated the lycopene accumulation of Persimmon fruits ( Ye et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%